The gratifications of cancer patients browsing health websites - A field study on a sample of patients in the city of M'sila- - جمال شريف,; رمضان بن منصور, (International Journal of Social Communication, 2022)
The study aimed to identify the gratifications achieved by patients with cancer in the city of M'sila by browsing various health websites, and the study included an intentional sample of 100 cancer patients in the city of M'sila, and the study reached the following most important results: The majority of patients browse the "Everyday Medical Information" website, Patients benefit from browsing in coexistence and dealing with their illness and treatment in some cases through alternative medicine,The absence of oversight and regulations for these sites is one of the most important difficulties they face ,also The abundance of information on health websites reinforces the fears of cancer patients.